Belajar dari Sejarah: Refleksi atas Warisan Kolonial dan Praktik Pelestarian Sumber Daya Alam di Indonesia - Tanaya, Haidar Trisna (Jurnal Sejarah Citra Lekha, 2023)
Indonesia has a long history of both exploitation and nature conservation. Even before the arrival of Western nations, the concept of conservation was known to the people. Despite Western colonialism, often being associated with natural exploitation, it is also contributed to various forms of nature conservation in Indonesia, some of which are still implemented today. This study was analyzed using historical methods with emphasis on the stages of source selection and source criticism. Based on this study, the fact is that natural conservation legacies such as nature reserves, national parks and wildlife sanctuaries are actually originated from the colonial government. The establishment of rules governing nature conservation during the colonial periodundersores the seriousness of their efforts in this regard. The existence of various nature conservation efforts carried out by the community before and during the Western colonialism serves as a reflection of Indonesia’s commitment to nature conservation efforts. Their efforts, including the process of establishing nature reserves and regulations in terms of conservation, provide valuable  lessons, especially when Indonesia is currently faced with various environmental and ecological issues and the threat of a natural crisis.